Strengths and Limitations of Pap Smear Screening: When Cytology Succeeds and Where it Fails - Bhagyashree; Rituraj; Prabhat Pant; Preeti Sharma (Online Journal of Health & Allied Sciences)
Background: Cervical cancer remains a significant global health concern, with early detection through Pap smear cytology playing a pivotal role in reducing morbidity and mortality. Objectives: This retrospective study evaluated the diagnostic accuracy of Pap smears in 2,746 cases, correlating cytological findings with histopathology in 158 cases. Methods: A retrospective analysis was conducted on 2,746 cervical cytology cases from year 2019 to 2024, categorized using the Bethesda System. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and chi-square tests were employed to assess cytology-histopathology concordance. Results: The study demonstrated high sensitivity (94.5%) and negative predictive value (90.3%), confirming the test’s reliability in ruling out disease. However, specificity was modest (50.9%), with frequent false positives in low-grade lesions (ASC-US: 55.6% discordance; AGC: 66.7% discordance), often due to benign mimics like cervicitis. High-grade lesions (HSIL, SCC, adenocarcinoma) showed perfect concordance (100%). Chi-square analysis revealed a significant association between cytology and histopathology (χ² = 87.42, p < 0.001), with subgroup analysis underscoring stronger correlations for high-grade lesions (HSIL/SCC: χ² = 42.36, p < 0.001). Conclusion: These findings highlight the Pap smear’s strength in detecting clinically significant lesions while emphasizing the need for adjunctive tests (e.g., HPV testing) to improve specificity in ambiguous cases.